Analyse physico-chimique de l'eau de mer au niveau de quelques sites de rejets des eaux usées – Côte de Mostaganem - Zakaria Imad Eddine, FATMIA (My University, 2020)
This work aimed to analyze the physical and chemical parameters of the seawater under the influence of wastewater discharges coming from the wastewater treatment plant located near the Crique of Salamandre, on the one hand, and wastewater discharges in the beach of Stidia, on the other hand. The measurements were carried out using a portable multi-parameter probe and allowed to give an opinion on the quality of the sampled seawater by comparing it with reference seawater. Of the four sites chosen for sampling, only two were selected (Stidia beach and Crique of Salamandre) since other targeted beaches were closed due to the sanitary situation (Covid-19). Stidia beach was used as a reference site due to the fact that the spills were low in this location. Water samples were taken during the months of March and July 2020. Five physical and chemical parameters were analyzed, namely temperature and dissolved oxygen, measured in situ, salinity, conductivity and hydrogen potential which have been determined in the laboratory. The results of the study show that the seawater sampled at the Crique of Salamandre is affected by daily discharges from the wastewater treatment plant (STEP), whose treatment seems to be insufficient. In a concern for the protection of the Crique of Salamandre and the ecosystems established in it, the STEP of Mostaganem should improve its treatment efficiency.
Keywords: physical and chemical parameters; treated water; STEP; wastewater; marine environment.